COMPARATIVE BETWEEN THE ENGINE DEVELOPMENT PROFILE OF REPRESENTATIVE REPEAT STUDENT AND NON-REPEAT SCHOOLS IN THE INITIAL YEARS OF FUNDAMENTAL TEACHING (Fiep Bulletin - online, 2017)
The purpose of this researchto compare the motor profile of schoolchildren from the initial years of Elementary Schoolwho have undergone repetition with non-repeating children. It sought to understand the need to overcome some paradigms thatare invigorating in the daily school life, which can influence the teaching and learning process. The population was composed ofchildren enrolled in the public network, and the sample was organized into two groups: experimental and control. TheExperimental Group - 40 children from 7 to 11 years of chronological, who had at least one repetition in some series. The Controlgroup of the same number of schoolchildren, with the same chronological ages and gender, without repetition. These groupswere applied the Motor Development Scale protocol - Rosa Neto (2002). Thus, the indicators were constructed to analyze thepreviously defined parameters: Steps to estimate the motor profile of schoolchildren. The results showed that there is a differencebetweenthe chronological and motor ages, (IMG
Keywords: Learning. Motricity. Human development